(393) Some Remarks on Capital Output Ratio بعض الملاحظات حول نسبة الناتج الرأسمالي - Zaki, Ramzi (معهد التخطيط القومى, 2024)
This study aims to analyze the concept of the capital-output ratio and its importance in economic planning. It also explores international comparisons of this ratio, particularly between developing and developed countries. The research covers the definition of the capital-output ratio, its role in economic planning, comparative studies, and its limitations. The study highlights that this concept is ambiguous due to varying definitions provided by economists. E.D. Donar defines the ratio as the relationship between capital stock and the output produced, which can apply to the overall economy, specific sectors, industries, or process